2021
DOI: 10.1002/pc.26444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive pomace particles content on mode I and mode II delamination fracture of S‐glass fiber reinforced composites

Abstract: This work aims to investigate the effect of micro-sized olive pomace (OP) particle incorporation on the mode I and mode II delamination fractures of glass fiber reinforced polymer composites. In this way, it is possible to recycle the natural OP materials and benefit from the development of high performance engineering polymer matrix composites in industrial applications as well as producing low cost composite. For this purpose, six different OP weight ratios (0%, 0.5%, 1%, 5%, 10%, and 15%) were used for modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Bulut et al studied inter-laminar fracture toughness(mode I and mode II) test on micro sized olive pomace reinforced S-glass composite and reported that load bearing capability was improved by 13.8% and 60.4%, respectively as an combined effect of natural and synthetic fibers in the polymer composite. 13 From an application perspective, Mansor et al studied on hybrid natural and GFs reinforced polymer composites for use in automotive component construction. 14 To this end, it is postulated that fiber hybridization (GF, AF, and RF) will strengthen the polymer matrix and enhance the resulting physical and mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Bulut et al studied inter-laminar fracture toughness(mode I and mode II) test on micro sized olive pomace reinforced S-glass composite and reported that load bearing capability was improved by 13.8% and 60.4%, respectively as an combined effect of natural and synthetic fibers in the polymer composite. 13 From an application perspective, Mansor et al studied on hybrid natural and GFs reinforced polymer composites for use in automotive component construction. 14 To this end, it is postulated that fiber hybridization (GF, AF, and RF) will strengthen the polymer matrix and enhance the resulting physical and mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a viable solution to address these limitations involves incorporating highly ductile particulate fillers, which can be achieved by controlling the foam's relative density, cell size, and the composite's anisotropy. [22][23][24][25] Numerous studies have demonstrated that the inclusion of nanoparticles, such as CNTs and silica, can effectively enhance the mechanical properties of PU foams. [26][27][28] For example, Ghosh et al found that incorporating small amounts of inorganic lamellar clay minerals composed of layered silicates can significantly enhance the mechanical properties of the PU foam substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limited energy absorption capability of purely flexible PU foams restricts their potential applications. Consequently, a viable solution to address these limitations involves incorporating highly ductile particulate fillers, which can be achieved by controlling the foam's relative density, cell size, and the composite's anisotropy 22–25 . Numerous studies have demonstrated that the inclusion of nanoparticles, such as CNTs and silica, can effectively enhance the mechanical properties of PU foams 26–28 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of thermal cycle fatigue on the curvature and residual stresses of nanocomposite laminates was investigated by Tabatabaeian and Ghasemi. [7] One of the major problems with composite materials is deboning between their constituents namely delamination which has led to much research devoted to the study of this phenomenon in composites [8][9][10][11][12][13][14] . Such a failure stems from the propagation of preexisting cracks or the formation of new cracks along with the material interfaces.…”
Section: Introductionmentioning
confidence: 99%